Genotypic distribution and molecular epidemiology of HPV in women in the UAE using PNA-based RT PCR - Devapriya Finney; Ahmed Luay Osman Hashim; Sunil Kumar Bylappa; Ameena Ebrahim Mugar; Manivannan Nandhagopal; Mohammed Abdulrazzaq Jabbar; Nazeerullah Rahamathullah (PLoS ONE, 2026)
Objectives This study aimed to determine the genotypic distribution and molecular epidemiology of HPVs in PAP smear samples of women in the UAE using a peptide nucleic acid (PNA)-based fluorescence melting curve analysis method. Methods A cross-sectional retrospective study was conducted between January 2024 to January 2025 after receiving ethical approval from the Institutional Review Board of Gulf Medical University. A total of 229 liquid-based cervical cytology samples were obtained from women aged 20–55 years attending the Gynaecology out-patient department of Thumbay University Hospital and other hospitals of the UAE, processed for the routine cytological examination to identify and differentiate morphological changes of the PAP smears. HPV genotyping was performed using PNA-based fluorescence melting curve analysis by the RT-PCR method. Results A total of 191 HPV genotypes were detected in 96 HPV positive PAP smear samples, including 47 abnormal cytology and 49 NILM samples. 137 HR and 54 LR-HPV genotypes were identified in all 96 positive samples. The highest rate of mixed HR and LR-HPV genotypes (18%) was detected in women aged 31–40 years old. HR53, 16, 68, 66, 31, 35, and LR6 were the predominant genotypes. Mixed HR and LR-HPV infection is present in 26% cases; in that HPV53 was the primary genotype, followed by HPV35, 66, 11, 43, 81, 61, and 6. Conclusion The genotypes 53, 16, 68, 66, 31, 61, 35, and 6 were the most common genotypes detected in the PAP smear samples. Notably, 21% of normal epithelial cells of the PAP smear samples tested positive for different HR-HPV genotypes. These findings underscore the crucial role of HPV genotyping using RT-PCR, enhancing the effectiveness of screening surveillance and providing foundational data for future prospective studies, vaccination impact assessments, and targeted screening strategies.